(untitled) (The Peerian Journal, 2022)
Scientific researches on textual studies and literary source studies play an important role in conveying the world of topics related to humanity and its rich spiritual heritage to the people by demonstrating the power and possibilities of fiction in words. In the article, the language features of the epic "Bahrom and Gulandom", aspects of the use of artistic arts, and the creative skills of the author of the prose translation are shown on the basis of artistic analysis. In this respect, this work is a practical contribution to the above research